2016
DOI: 10.4238/gmr.15038717
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of AMPD1, CPT2, and PGYM metabolic enzymes in patients with chronic fatigue syndrome

Abstract: ABSTRACT. Chronic fatigue syndrome (CFS) is a disease that can seriously impair one's quality of life; patients complain of excessive fatigue and myalgia following physical exertion. This disease may be associated with abnormalities in genes affecting exercise tolerance and physical performance. Adenosine monophosphate deaminase (AMPD1), carnitine palmitoyltransferase II (CPT2), and the muscle isoform of glycogen phosphorylase (PYGM) genes provide instructions for producing enzymes that play major roles in ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Many other studies found a significant association between ME/CFS and polymorphisms in the disrupted‐in‐schizophrenia 1 gene (DISC1), with copy number variants in genes associated with the function of the central nervous system, as well as with polymorphisms in ion channels and acetylcholine receptors, as well as with previously mentioned polymorphisms in HLA class I and class II loci 188–191 . One more study examined the contribution of AMPD1 , CPT2 , and PGYM genes, but no significant association was detected with CFS 192 . In addition, polymorphisms in neuroendocrine effector and receptor genes like TPH2 , COMT , and NR3C1 were found to predict the development of CFS 193 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other studies found a significant association between ME/CFS and polymorphisms in the disrupted‐in‐schizophrenia 1 gene (DISC1), with copy number variants in genes associated with the function of the central nervous system, as well as with polymorphisms in ion channels and acetylcholine receptors, as well as with previously mentioned polymorphisms in HLA class I and class II loci 188–191 . One more study examined the contribution of AMPD1 , CPT2 , and PGYM genes, but no significant association was detected with CFS 192 . In addition, polymorphisms in neuroendocrine effector and receptor genes like TPH2 , COMT , and NR3C1 were found to predict the development of CFS 193 .…”
Section: Resultsmentioning
confidence: 99%
“…[188][189][190][191] One more study examined the contribution of AMPD1, CPT2, and PGYM genes, but no significant association was detected with CFS. 192 In addition, polymorphisms in neuroendocrine effector and receptor genes like TPH2, COMT, and NR3C1 were found to predict the development of CFS. 193 Twenty-one variants harbored in 13 different genes (FAM126B, TCF3, EIF3A, UBTF, METTL3, SORL1, IL6ST, PNPLA6, BMP2K, ARSD, GSN, HIF1A, and PEX16) were also associated with ME/ CFS in the context of one more study.…”
Section: Findings From Genetic Association and Cohort Studies Of Me/cfsmentioning
confidence: 99%